The contribution of forensic dentistry in human identification: A narrative review (Research, Society and Development, 2025)
Forensic odontology analysis is of utmost importance for human identification, especially in situations where DNA analysis methods or fingerprints become unfeasible. The objective of this article is to discuss the relevance and multiple applications of Forensic Dentistry in the human identification process, focusing on the comparative use of ante-mortem and post-mortem dental data as the main identifying method in forensic scenarios with compromised remains. This study is a narrative review of the literature with articles published from 2016 to 2024, through consultations in the databases of the National Library of Medicine (PubMed/MEDLINE), Latin American and Caribbean Literature in Health Sciences (LILACS), and Science Direct, with 12 articles selected for the research. The adopted methodology allowed the categorization of evidence in different forensic approaches, such as the use of radiographs, plaster models, dental implants, and absence of elements, and digital overlay techniques. The results demonstrated that elements such as updated dental records, procedures like restorations, and implant records are decisive in identifying victims, even under adverse conditions like carbonization or decomposition. Thus, it is concluded that the standardization of dental records and the adoption of digital technologies strengthen forensic action, consolidating Forensic Dentistry as an effective, ethical, and accessible tool in defense of the right to identity.